Spiritual care competencies among nursing students in the middle East and Asia: a systematic review - Inggriane Puspita Dewi; Hartiah Haroen; Hana Rizmadewi Agustina; Tuti Pahria; Nita Arisanti; Preeya Keawpimon (BMC Nursing)
Abstract Spiritual care is recognized as a crucial component of holistic nursing education, significantly enhancing patient well-being, health outcomes, and decision-making. However, a systematic evaluation of spiritual care education programs in the Middle East and Asia remains limited. This systematic review aims to assess the effectiveness of spiritual care education programs in enhancing undergraduate nursing students’ competencies in these regions. Following PRISMA-P guidelines and registered on PROSPERO (CRD42024552137), the study employed the PICOS framework for selection criteria: Participants (undergraduate nursing students), Intervention (spiritual nursing education programs), Comparison (education without spiritual content), Outcomes (spiritual care competencies), and Study design (RCT or quasi-experiment). Searches were conducted in Cochrane, Medline, PubMed, Sage, and Scopus from April to May 2024. Multiple reviewers independently performed data extraction and quality assessment using ROB 2 and ROBIN-I tools. A narrative synthesis approach explored data relationships and theoretical applications. Out of 1,350 reviewed articles, 10 studies involving 749 nursing students from Iran, Taiwan, and Turkey met the inclusion criteria. The interventions spanned from one month to a full semester and combined theoretical learning with clinical practice. The findings indicate that education in spiritual care significantly enhances students’ self-awareness, knowledge, attitudes, and practical skills. The study emphasizes the importance of incorporating spirituality into nursing curricula to promote a holistic approach to patient care. Limitations of the study include differences in study designs, selection bias, variability among participants, and reliance on self-reported data. Future research should aim for longitudinal studies to evaluate long-term effects and create culturally sensitive assessment tools for measuring spiritual competencies.